Re-weighting EUROMOD for demographic change: An application on Slovenian and Lithuanian data - Nataša Kump; Jekaterina Navicke (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper discusses an application of re-weighting to account for demographic change within a comparative micro-simulation setting. We use the Slovenian and Lithuanian components of the EUROMOD micro-simulation model with data referring to demographic characteristics of the population in 2010 to test the proposed procedures. The data are re-weighted to reflect demographic change up to 2012 and 2020 as indicated in the Eurostat Population Projections (Europop).
Keywords: C81; D31; I32; 330; microsimulation; re-weighting; demographic change; Slovenia; Lithuania